2019
DOI: 10.1111/eea.12752
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐kingdom signaling — symbiotic yeasts produce semiochemicals that attract their yellowjacket hosts

Abstract: In recent studies, the yeast species Hanseniaspora uvarum and Lachancea thermotolerans were isolated from the digestive tract of four North American yellowjacket species (Hymenoptera: Vespidae), and attraction of yellowjackets to brewer's yeast, Saccharomyces cerevisiae (all Saccharomycetaceae), growing on fruit powder was demonstrated. We tested the hypothesis that Vespula spp. are attracted to cultures of H. uvarum and L. thermotolerans and their respective volatiles. In field experiments, we found that H. u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…In addition to ethyl acetate, 10 esters were unique for the volatile blends of H. uvarum yeasts; these compounds originated from amino acid synthesis and degradation pathways [66]. Prevalence of esters in volatile blends of H. uvarum has been reported in previous studies [70,71]; however, ethanol being the third largest component of the blend in our experiments, has not been determined by Babcock et al [71] or Piper et al [70]. High production of ethanol, 3-methylbutanol, 2-phenylethanol, ethyl acetate, and 3-methylbutyl acetate were reported for M. pulcherrima and A. pullulans yeasts [15].…”
Section: Discussionmentioning
confidence: 87%
“…In addition to ethyl acetate, 10 esters were unique for the volatile blends of H. uvarum yeasts; these compounds originated from amino acid synthesis and degradation pathways [66]. Prevalence of esters in volatile blends of H. uvarum has been reported in previous studies [70,71]; however, ethanol being the third largest component of the blend in our experiments, has not been determined by Babcock et al [71] or Piper et al [70]. High production of ethanol, 3-methylbutanol, 2-phenylethanol, ethyl acetate, and 3-methylbutyl acetate were reported for M. pulcherrima and A. pullulans yeasts [15].…”
Section: Discussionmentioning
confidence: 87%
“…Lachancea thermotolerans and its semiochemicals, respectively, also attract several species of North American yellowjackets (Hymenoptera: Vespidae) [54,55] and the green lacewing, Chrysoperla comanche (Stephens) [56]. When grown and aerated on grape juice agar, L. thermotolerans produced 20 odorants which, when field-tested as a synthetic blend, attracted Western yellowjackets, Vespula pensylvanica [54].…”
Section: Discussionmentioning
confidence: 99%
“…In North American yellowjacket wasps (Hymenoptera, Vespidae), two species of fungi produce VOCs that attract conspecific individuals. Hanseniaspora uvarum and Lachancea thermotolerans were attractive to three species of yellowjacket wasps (V. pensylvanica, V. germanica, and V. alascensis) when grown on grape juice-infused yeast peptone dextrose (YPD) agar [38]. Gas chromatography-mass spectrometry analysis revealed that ethyl acetate (only H. uvarum), phenylethyl acetate, isoamyl acetate, 2-phenylethyl alcohol, isoamyl alcohol, and 2-methyl-butanol were the most abundant headspace volatiles produced by these yeasts.…”
Section: Bacteria and Eusocial Insect Communicationmentioning
confidence: 99%
“…Gas chromatography-mass spectrometry analysis revealed that ethyl acetate (only H. uvarum), phenylethyl acetate, isoamyl acetate, 2-phenylethyl alcohol, isoamyl alcohol, and 2-methyl-butanol were the most abundant headspace volatiles produced by these yeasts. This information was instrumental to formulate a synthetic blend that was proven to be effective in attracting V. pensylvanica, but not the other yellowjacket species [38].…”
Section: Bacteria and Eusocial Insect Communicationmentioning
confidence: 99%